Attitudes of university students in the health field related to suicidal behavior (Research, Society and Development, 2021)
Attitudes related to suicidal behavior among health university students can impact the search for help, as well as assistance to people with suicidal behavior. Thus, the present study aimed to analyze the attitudes related to suicidal behavior among undergraduate health students and the associated factors. Cross-sectional, quantitative study, carried out in 2018 with 747 university students from a higher education institution located in the south of Minas Gerais. For data collection, a sociodemographic, educational and clinical questionnaire was self-administered; the Attitude Questionnaire towards Suicidal Behavior; Herth's Hope Scale; the Suicide Risk Assessment of the Neuropsychiatric Mini-interview; the Major Depression Inventory and the Rosenberg Self-Esteem Scale. The data were submitted to descriptive statistical analysis, mean comparison test, correlation and multiple regression. The predictors of negative feelings related to suicidal behavior were: female gender, not participating in religious activities, less perception of professional competence and moralistic attitudes. They were predictors of self-perceived professional competence: having a mental disorder, having more hope, having a risk of suicide, having no religion or spirituality, less negative feelings and moralistic attitudes. The predictors of greater understanding of the right to suicide were not participating in religious activities, being diagnosed with a mental disorder, reading specific material about suicide, having less negative feelings, less hope and less perception of one's professional ability. The study provides knowledge to support actions to promote professional training to qualify assistance to people with suicidal behavior.